Quality Characteristics of Mobile Applications: A Survey in Brazilian Context - Maia, Vitor; Gonçalves, Taisa G.; da Rocha, Ana Regina C. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
Mobile devices and their applications became popular since the creation of the app stores' distribution model. There is a great variety of apps available and we are inclined to use the best ones, what makes it essential to develop apps of distinctive quality. This paper described the execution and the results of a survey on the quality characteristics of mobile applications. The questions in the survey were based on the results of a previously conducted systematic mapping study, which identified occurrences of quality characteristics in the context of mobile applications. At all 500 answers were obtained. The analysis of these answers led to several results upon the opinion and preferences of users when using mobile applications. Usefulness and Functional Correctness were the most pertinent quality characteristics in the respondent's opinion. We expect that the outcomes of this study will help the development and the quality evaluation of mobile applications.